(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The lexical structure of the modern Karakalpak literary language has systematic differences in the structure, composition (positive, compound), lexical layer (both lexical layer and assimilation words). The construction of legal terms in the Karakalpak language is based on both internal and external influences, and is based on the model base, language analogy, which is formed in the construction of terms. When learning the formation of legal terms in the Karakalpak language, it can be seen that the word was formed by several models of formation and took its place in the language.